Optoacoustic signal excitation with a tone-burst of short pulses - X.L. Deán-Ben; D. Razansky (Photoacoustics, 2018)
Individual light pulses with durations in the nanosecond range are most often employed in biomedical optoacoustic imaging. In this excitation regime, ultra-wideband acoustic responses are generated from tissues that cannot be efficiently captured with ultrasound transducers having a limited detection bandwidth. Here, we analyse a narrowband optoacoustic signal excitation mechanism consisting of a tone-burst of multiple equally-delayed pulses. The signal generation efficiency of single-pulse versus tone-burst excitation is compared for normal light exposure levels in the linear optoacoustic signal generation regime as well as when considering non-linearities associated with temperature increase or absorption saturation. The signal-to-noise ratio of the excited signals is also experimentally compared using a highly-absorbing ink phantom.